The Impact of COVID-19 on Bank Sector Traditional Business Model Sustainability in China: Bank Branch Versus Fintech - Yan, Jingshi; Jia, Pan (Frontiers in Physics, 2022)
This paper aims to analyze the impact of COVID-19 on the sustainability of the banking sector and the fintech sector. In China, where banks' revenue mainly comes from branches, we collect relevant data manually and use the OLS model for empirical analysis. The results show that as the COVID-19 infection rate increases, the number of bank branches decreases significantly, which threatens the banking sector's sustaina-bility. The fintech sector acts as a competitor to the banking sector. With the increase of COVID-19 infection rate, the public pays more atten-tion to fintech, promoting the development of the fintech sector. Moreover, the impact of COVID-19 on these two sectors will diminish over time. In addition, this paper finds that COVID-19 further weakens the number of bank branches during the epidemic through the mediating effect of fintech. The findings of this paper help to assess the sustainability of the different financial sectors during the epidemic, which is es-sential for financial stability.